Application of second-harmonic electro-optical measurements in the study of polar liquid crystal phases. Issue 12 (25th September 2016) - Nowicka, K.; Knapkiewicz, M.; Bielejewska, N.; Dardas, D.; Kuczyński, W.; Hoffmann, J.
ABSTRACT: The chiral smectic phases of two liquid crystals (LCs) were investigated, one of them is a high tilted, long pitch, near ortoconic LC mixture and the second exhibits broad temperature of the phase. For both materials second-harmonic electro-optic (EO) spectra were studied. The particular LC phases were characterised by a specific temperature dependence of the frequency at which the real part of the second-order electro-optic response (EOR) possesses an extremum ( f ext ). The obtained values of f ext (correlated with the phase-type mode processes) were used to identify LC phases and temperature of phase transitions. The sensitivity of the used method allowed to identify the and phases for the studied materials, not detected before by DSC or dielectric measurements. GRAPHICAL ABSTRACT: